PEMANFAATAN MEDIA PAPAN PINTAR UNTUK MENINGKATKAN NUMERASI BERHITUNG SISWA KELAS 1 DI SD INPRES DHEREISA - Efrida Ita; Marsianus Meka; Elisabeth Tantiana Ngura; Oktaviani Gulo (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This research aims to improve the numeracy skills of grade 1 students at SD Inpres Dhereisa in learning mathematics using the Smart Counting Board. This type of research is Classroom Action Research (PTK). This research consists of 2 cycles. The subjects of this research were 25 grade 1 students at SD Inpres Dhereisa, consisting of 12 male students and 13 female students. The data collection method uses tests. The data collected in this research is in the form of quantitative data, namely the main data in the research in the form of important assessment data on numeracy ability tests. The results of research on the use of smart board media for counting in mathematics learning with addition and subtraction material from 1-30 stated that it increased after using smart board media from pre-cycle to cycle 1 by 12% and obtained an average pre-cycle score of 52.4 to cycle one. -an average of 64.4 or in the sufficient category. From cycle 1 to cycle 2 there was an increase of 17.2% and obtained an average score of 81.60 or in the very good category. Meanwhile, classically there was a very significant increase, namely reaching 100% from the KKM determination of 70%. This indicates that the use of smart numeracy board media is very effective in improving numeracy skills in grade 1 students at SD Inpres Dhereisa.